Policy, Investment, and Organizational Readiness as Determinants of Electronic Medical Record Adoption in Primary Healthcare Clinics - Darsono, Susilo Nur Aji Cokro; Zahra, Annisa Az; Rahman, Ferry Fadzlul; Syelvia, Delvi (Universitas Muhammadiyah Yogyakarta, 2026)
Indonesia mandated the implementation of Electronic Medical Records (EMR) in all healthcare facilities through Minister of Health Regulation No. 24 of 2022, requiring full adoption by December 31, 2023. However, variations in implementation across primary healthcare facilities remain evident. This study aimed to analyze factors associated with the level of EMR adoption in clinics at level-1 healthcare facilities in Bantul Regency, Indonesia. A quantitative cross-sectional study was conducted using structured questionnaires distributed to clinic officials in primary healthcare clinics that had implemented EMR systems. Data were collected from 51 respondents representing 35 clinics between January and February 2024. The variables examined included top management beliefs, top management participation, public policy, investment, and organizational performance. A multiple linear regression analysis in SPSS version 22 was conducted to examine the relationships between these variables and the EMR adoption rate. The findings show that top management beliefs, public policy, investment, and organizational performance are significantly associated with the EMR adoption rate. In contrast, top management participation does not demonstrate a statistically significant relationship with adoption levels. Among the examined variables, investment and public policy show the strongest influence, highlighting the importance of financial readiness and supportive regulatory frameworks in facilitating EMR implementation. EMR adoption in primary healthcare clinics is largely driven by policy support, organizational capacity, and investment in health information technology. Strengthening regulatory implementation, providing clearer guidance, and ensuring sustainable funding are essential to accelerate digital health transformation. Future research should examine broader implementation outcomes such as usability, workflow integration, and healthcare service quality.